Isolation and characterization of mercury-resistant microbes from gold mine area in Mount Pongkor, Bogor District, Indonesia - Wilhelmus Terang Arga Sanjaya; Nur Syafira Khoirunhisa; Sri Ismiani; Fahrizal Hazra; Dwi Andreas Santosa (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Sanjaya WTA, Khoirunnisa NS, Ismiani A, Hazra F, Santosa DA. 2021. Isolation and characterization of mercury-resistant microbes from gold mine area in Mount Pongkor, Bogor District, Indonesia. Biodiversitas 22: 2656-2666. Exploring novel wild-type microbes is very important to give more flexibility for bioremediation implementation. It is related to discovering strain with higher detoxification ability and more reliable degradation mechanisms. Moreover, novel strain can be used as genetic material for strain development by molecular genetic engineering and production design formulation. The aims of this experiment were to characterize and identify new mercury-resistant microbes, investigate their capacity to accumulate mercury, and analyze the reducing mercury toxicity in bioassay. Four strains of bacteria selected through the screening stage were characterized for their morphological, biochemical, physiological, and molecular genetic characteristics. Considering their characteristics and mercury resistance levels, there are two selected microbial strains: fungus strain Cladosporium halotolerans Hg32 and the bacterial strain Mycolicibacterium peregrinum Hg37 with a mercury resistance level up to 3000 mg L-1. The C. halotolerans Hg32 could remove mercury with the highest potency up to 90.72% at a mercury concentration of 100 mg L-1, while  M. peregrinum Hg37 removes up to 77.10% at mercury concentrations of 10 mg L-1. Toxicity bioassay tests using fish confirmed that C. halotolerans Hg32 and M. peregrinum Hg37 had the ability to detoxify mercury in contaminated water. Both have successfully proven to reduce the mortality rate to below 5%.